Using the intact periosteum for horizontal bone augmentation of peri-implant defects: a retrospective cohort study. Issue 10 (December 2022) - Deng, Chen; Yi, Zumu; Xiong, Chenyi; Man, Yi; Qu, Yili
Abstract: The objectives of this study were to observe hard tissue changes in guided bone regeneration (GBR) with intact periosteum and soft block deproteinised bovine bone mineral (DBBM), and evaluate whether the result of horizontal bone augmentation varied by initial peri-implant defect depth. Forty patients with a single missing tooth and contained peri-implant defect were categorised into three groups according to their presurgical defect depth (≤ 2, 2–4, and 4–6 mm). Cone-beam computed tomography (CBCT) images were collected and reconstructed preoperatively, postoperatively, and at six months' follow up. The buccal bone width (BBW -0, -3, -5), alveolar bone width (ABW -0, -3, -5) and volume of augmented area were measured. At the six-month follow up the increase in BBW, ABW at all levels, and in bone volume, was statistically significant (all p < 0.001). No statistical significance in bone dimensions or bone resorption was found among groups (all p > 0.05). Histological analysis detected new bone formation in intimate contact with bone grafts underlying the periosteum. Within the limitations of this study, the insights gained may be of assistance to suggest that comparable and acceptable results of horizontal bone augmentation can be achieved in cases of peri-implant defect depth of ≤6 mm by means of GBR with intact periosteum.